Promoting diversity tolerance among Indonesians through smart mobile civic media in Citizenship Education - Trisiana, Anita; Triyanto, Triyanto; Zakaria, Gamal Abdul Nasir; Sakinah, Sakinah; Arvinth, N (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
The formation of student characters is carried out with variations in the form of digital-based "Smart Mobile Civic" learning media innovations that can be applied to learning civic education. It is hoped that this innovation has the potential to improve critical, rational, and creative thinking skills following Pancasila's values in responding to various problems in the field of citizenship. This research aims to (1) analyse the implementation and improvement of tolerance character. (2) analysis of the effectiveness of the tolerant values applied in Smart Mobile Civic. The research results show that: (1) Lecturers act as presenters and models for students to develop good values. (2) Smart Mobile Civic is an effective medium for efforts to form an attitude of tolerance shown through the learning achievements of citizens' rights and obligations in maintaining the integrity of the Unitary State of the Republic of Indonesia. The diversity of Indonesian society as a Unitary State is integrated with the Teaching Module developed with the Smart Mobile Civic application. It is very relevant to the demands of digitalisation of citizenship education learning technology as a form of increasing "civic disposition" competence, which develops attitudes as a form of implementing citizenship education and achieving the Pancasila student profile, namely having six main characteristics: faith, devotion to God Almighty, and noble character, global diversity, cooperation, independence, critical thinking and creativity.